Ankyloglossia and Lingual Frenotomy: National Trends in Inpatient Diagnosis and Management in the United States, 1997‐2012. (7th February 2017) - Walsh, Jonathan; Links, Anne; Boss, Emily; Tunkel, David
Abstract : Objectives: (1) Describe trends in the diagnosis of ankyloglossia and the use of lingual frenotomy and (2) analyze patient‐ and hospital‐level factors as compared with the total pediatric discharge population. Study Design: National database analysis. Methods: We reviewed available data from 1997 to 2012 using the Kids' Inpatient Database, Healthcare Cost and Utilization Project, Agency for Healthcare Research and Quality. All weighted pediatric discharges with ankyloglossia, newborn feeding difficulty, or lingual frenotomy were analyzed for variables of sex, payer, zip code median income, hospital ownership, location/teaching status, bed size, region, and children's hospital status. Chi‐square analysis with 95% CIs and odds ratio were used to identify differences between the study group and the total database discharge population. Results: Diagnosis of ankyloglossia increased each year of publication (every third year)—with 3934, 5430, 7785, 11, 397, 19, 459, and 32, 837 children, respectively, from 1997 to 2012—with the largest increase in the last 6 years. Similarly, frenotomy increased with 1279, 1633, 2538, 3988, 6900, and 12, 406 procedures. Compared with the total discharge population, children with ankyloglossia or frenotomy were more often male (63.6% ankyloglossia, 65.3% frenotomy vs 51.2%), privately insured (60.1%, 62.1% vs 43.6%), from a higher median‐income zip code (78.1%, 78.2% vs 68.6%), and in Midwest region (29.3%, 32.3% vs 21.7%). Conclusion: These pilot data show increases in diagnoses of ankyloglossia and use of frenotomy. There is a preponderance of children who are male, privately insured, or Midwest residents being diagnosed and treated for ankyloglossia. This broad variation may reflect local practice patterns or imply cultural and socioeconomic bias.